The GOLMePsA study protocol: an investigator-initiated, double-blind, parallel-group, randomised, controlled trial of GOLimumab and methotrexate versus methotrexate in early diagnosed psoriatic arthritis using clinical and whole body MRI outcomes - De Marco, G; Helliwell, P; McGonagle, D; Emery, P; Coates, L; Hensor, E; Marzo-Ortega, H (BioMed Central, 2017)
Psoriatic arthritis (PsA) is a chronic inflammatory arthritis which impacts significantly on the quality of life and work capacity of affected individuals. Recent evidence has shown that early control of inflammation in PsA leads to improved long-term outcomes. It is postulated that prompt intervention after diagnosis using a remission-induction treatment strategy will lead to improved outcomes and optimal disease control of PsA. The aim of the present study was to compare the clinical efficacy of a treatment strategy in newly diagnosed, treatment naïve PsA subjects, using the combination of golimumab (GOL), methotrexate (MTX) and steroids versus standard care (MTX monotherapy plus steroids). Methods/design: GOLMePsA is an investigator initiated, phase IIIb, single-centre, randomised, double-blind, placebo-controlled, two-armed, parallel-group, imaging-supplemented study. Eighty-eight PsA patients, diagnosed within 24 months prior to screening and treatment naïve, will be randomised at baseline to receive: (arm 1) the combination of intramuscular/intra-articular prednisolone, MTX and GOL or (arm 2) the combination of intramuscular/intra-articular prednisolone, MTX and placebo for 24 weeks (interventional period). Primary outcome measure is clinical improvement (at least 1 unit difference) in the Psoriatic ArthritiS Disease Activity Score (PASDAS) composite index. Reflecting a “step down” therapeutic approach, all participants successfully completing the interventional period will be followed up for a further 28 weeks. During this observational period, stable maintenance MTX monotherapy will continue for both arms, unless in case of intolerance or PsA relapse. In the latter case, additional treatment will be provided. Overall, the GOLMePsA study length is planned to be 52 weeks. Discussion: The hypothesis underlining this study is that very early treatment with first-line GOL reduces disease activity in PsA, in comparison to conventional therapy. Trial registration: EudraCT 2013–004122-28. 24/09/2013.